Elucidating the key role of the fungal mycelium on the biodegradation of n-pentane as a model hydrophobic VOC. (August 2016) - Vergara-Fernández, Alberto; Scott, Felipe; Moreno-Casas, Patricio; Díaz-Robles, Luis; Muñoz, Raúl
Abstract: The role of the aerial mycelium of the fungus Fusarium solani in the biodegradation of n -pentane was evaluated in a continuous fungal bioreactor (FB) to determine the contribution of the aerial (hyphae) and non-aerial (monolayer) fungal biomass. The experimental results showed that although the aerial biomass fraction represented only 25.9(±3)% on a dry weight basis, it was responsible for 71.6(±4)% of n -pentane removal. The FB attained a maximum elimination capacity ( EC max ) of 680(±30) g m −3 h −1 in the presence of fungal hyphae (which supported an interfacial area of 5.5(±1.5) × 10 6 m 2 m −3 ). In addition, a mathematical model capable of describing n -pentane biodegradation by the filamentous fungus was also developed and validated against the experimental data. This model successfully predicted the influence of the aerial biomass fraction and its partition coefficient on the n -pentane removal, with EC decreasing from 680(±30) g m −3 h −1 to values of 200(±14) g m −3 h −1 when the dimensionless partition coefficient increased from 0.21(±0.09) with aerial biomass to 0.88(±0.06) without aerial biomass. Highlights: The role of aerial and non-aerial fungal biomass of n -pentane biofiltration is assessed. In terms of dry weight, aerial biomass accounts for 26% of the total biomass. Aerial biomass is responsible for 71% of n -pentane elimination. A model of fungal biofiltration considering the aerial biomass was developed. The model points to biomass surface area and n -pentane partition coefficient as key parameters.